Aplikasi Forecasting Stok Barang Menggunakan Metode Weighted Moving Average (WMA) pada Metrojaya Komputer - Imam Solikin; Septa Hardini (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Metrojaya Komputer is a business engaged in buying and selling, the purchasing process often has difficulty in determining how much stock of goods must be purchased for the future period, because it has not used forecasting methods. Forecasting is a forecasting that requires the retrieval of historical data to be processed in order to produce a decision on what predictions are needed for the next period. The purpose of this research is to simplify and accelerate forecasting using the weighted moving average (WMA) approach through the development of information technology based systems. The data needed in forecasting is the previous period data, whether the previous month's data or the previous year, then processed using forecasting equation. Forecasting can be processed based on data from the previous three periods or based on a certain period to produce the required stock of goods. The system development method used is the waterfall method which consists of several stages of communication, planning, modeling, construction, and deployment. This study produces a forecasting information system with a weighted moving average (WMA) approach that can be processed using an information technology based system so that it makes it easier and faster in making decisions regarding the stock of goods needed in sales.